2017
DOI: 10.1021/acsnano.7b04752
|View full text |Cite
|
Sign up to set email alerts
|

Damage-Free Smooth-Sidewall InGaAs Nanopillar Array by Metal-Assisted Chemical Etching

Abstract: Producing densely packed high aspect ratio InGaAs nanostructures without surface damage is critical for beyond Si-CMOS nanoelectronic and optoelectronic devices. However, conventional dry etching methods are known to produce irreversible damage to III-V compound semiconductors because of the inherent high-energy ion-driven process. In this work, we demonstrate the realization of ordered, uniform, array-based InGaAs pillars with diameters as small as 200 nm using the damage-free metal-assisted chemical etching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 62 publications
(154 reference statements)
0
55
0
Order By: Relevance
“…Additionally, the presence of sulphur in the S-OA etch was found to have a passivating effect on surface dangling bonds for etched GaAs nanopillars. More recently, metalassisted chemical (wet) etching of InP nanopillars has also been reported to achieve well-controlled anisotropic etching without a measured increase in the density of surface electronic carrier traps [172].…”
Section: Sidewall Roughnessmentioning
confidence: 99%
“…Additionally, the presence of sulphur in the S-OA etch was found to have a passivating effect on surface dangling bonds for etched GaAs nanopillars. More recently, metalassisted chemical (wet) etching of InP nanopillars has also been reported to achieve well-controlled anisotropic etching without a measured increase in the density of surface electronic carrier traps [172].…”
Section: Sidewall Roughnessmentioning
confidence: 99%
“…Li et al also extended the MacEtch method to other semiconductors such as GaAs and InP. [158][159][160][161] In 1960, Turner [162] proposed that the wet etching of silicon in HF aqueous solution containing oxidants at OCP is an electrochemical process, in which silicon oxidation and dissolution takes place at local anode areas, while the oxidizing agent is reduced at local cathode areas. Turner suggested that an etch pit will form at sites where it is more anodic than cathodic, while a hillock will be produced at areas that are more cathodic than anodic.…”
Section: Formation Of Luminescent Porous Silicon By Macetch Of Siliconmentioning
confidence: 99%
“…According to our density function theory calculations, the SBH is about 1.253 eV which is very close to the experimental value, as shown in Figure a,b (Calculation details are shown in the Supporting Information). The barrier will trap the holes generated by the H 2 O 2 reduction (Figure b) although the etching process still hardly occurs as explained above.…”
Section: Resultsmentioning
confidence: 97%